Translator Training: What Translation Students Have to Say - Li, Defeng (Meta, 2002)
AbstractFollowing an earlier study by the same author on professional translators which appeared in Target 2000 (12:1 127-149), this article reports on an empirical study, based on both quantitative and qualitative data, on the learning needs of translation students, another major stakeholder in translator training. This study shows that contrary to a widely held assumption, the great majority of students taking translation did not and do not intend to be professional translators/interpreters. It is found that translation students prized training of both L1 and L2 before or during translation training, and that they preferred practice-oriented courses to theoretical courses. Also revealed in this study is that many students believe the current translation program does not reflect the market needs very well and that measures such as offering more practical courses, strengthening language training, teachers’ providing more detailed comments on assignments, etc., must be taken in order to improve the program. Based on such findings, a comparison with the earlier study on professional translators is made and pedagogical implications are also drawn in relation to some of the focal issues in translator training.